Studies on seed production of hybrid groupers in a hatchery system - Shigeharu Senoo; Sitti Raehanah Muhamad Shaleh; Yukinori Mukai (Universiti Malaysia Sabah, 2010)
Hybridization is a process of crossing two different species and the offspring are known as hybrids. When these hybrids have more superior characteristics than both parents, they are said to possess hybrid vigor or positive heterosis which is a breeding goal in aquaculture. Hybrids can exhibit many commercially preferable characteristics for aquaculture such as faster growth, better feed conversion, increased resistance to diseases, tolerance to crowded conditions, and more uniformity in size and form among other traits. In view of the good qualities that are Imparted in the offspring of such crosses, hybridization remains as one of the effective methods of selective breeding that can enhance production efficiency in aquaculture. The Significance of heterosis can be appreciated by the combination of useful parental qualities in hybrids of the first generation In terms of aquaculture production, and also the output from using these hybrids (if they are fertile) as a valuable resource for further selection. New hybrids have been successfully produced since 2005 at the Hatchery, BMRI, UMS. There are four types of hybrid that were produced at the Hatchery which are: Tiger Grouper, Epinephelus fuscoguttatus x Giant Grouper, E. lanceolatus (TGxGG); Orange-Spotted Grouper, E. coioides x Giant Grouper, E. lanceolatus (OGxGG); Orange-Spotted Grouper, E. coioides x Tiger Grouper, E. fuscoguttatus (OGxTG), and Mouse Grouper, Cromileptes altivelis x Tiger Grouper, E. fuscoguttatus (MGxTG). Among these four hybrids, the TGxGG has the highest market value for Hong Kong. At present, the wholesale price of TGxGG is RM80 - 120jkg for the Hong Kong market and this has made TGxGG to become the main species in grouper culture in Southeast Asia.